2021
DOI: 10.1371/journal.pcbi.1009215
|View full text |Cite
|
Sign up to set email alerts
|

Rigid-body fitting to atomic force microscopy images for inferring probe shape and biomolecular structure

Abstract: Atomic force microscopy (AFM) can visualize functional biomolecules near the physiological condition, but the observed data are limited to the surface height of specimens. Since the AFM images highly depend on the probe tip shape, for successful inference of molecular structures from the measurement, the knowledge of the probe shape is required, but is often missing. Here, we developed a method of the rigid-body fitting to AFM images, which simultaneously finds the shape of the probe tip and the placement of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…We note that the Global Search method is similar to that recently reported for the rigid-body fitting to HS-AFM data [ 19 ]. In that regard, our independent work distinguishes itself by the convenient implementation into the user-friendly BioAFMviewer software interface (see Discussion ).…”
Section: Design and Implementationmentioning
confidence: 84%
See 3 more Smart Citations
“…We note that the Global Search method is similar to that recently reported for the rigid-body fitting to HS-AFM data [ 19 ]. In that regard, our independent work distinguishes itself by the convenient implementation into the user-friendly BioAFMviewer software interface (see Discussion ).…”
Section: Design and Implementationmentioning
confidence: 84%
“…Parameters characterizing the tip shape should play a role in the optimization process of finding the best match between simulation and experimental AFM image. Recent studies of structural fitting to AFM images showed that optimal parameters can be determined only within a margin of uncertainty [ 19 , 24 ], which is due to the limited resolution of the imaging method. Within the BioAFMviewer interface the user can easily modify the tip-shape and observe the immediate effect on the computed AFM image, and, as we have shown previously, simulation AFM images which remarkably well reproduce experimental AFM images can thus be obtained [ 16 ].…”
Section: Design and Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…4 ), the experimental realization is highly challenging. On the other side, computational approaches including molecular modelling and simulations are inreasingly used to assist in understanding biomolecular high-speed AFM measurements [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%